Rancang Bangun Sistem Pembayaran Parkir Menggunakan RFID Berbasis Arduino - Sujono Sujono; Zulfikar Zulfikar; Afif Maulana (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
The issue of illegal parking in various urban areas often causes traffic congestion, disorder, and economic losses for official parking operators. One of the main causes of this phenomenon is the weakness of parking management systems and the lack of effective supervision. To address this issue, this research designs and develops an RFID (Radio Frequency Identification)-based parking payment system as a solution. Traditional parking payment systems, which often still rely on cash payments, also frequently cause problems such as transaction delays, difficulties in providing change, and dependence on small denominations. These issues can lead to inconvenience for parking users and increase the risk of errors in the payment process. To address these problems, this research designs and builds an RFID-based parking payment system. This research uses the Prototype Method, which is a software development method focusing on the creation of an initial version of the system to be developed, ensuring that the resulting solution can work well, meet user needs, and be successfully implemented in a real-world environment. Based on the research findings, the RFID parking payment tool functions well. The results show that the RFID-based parking payment system is an effective solution for improving efficiency in parking payments.